Improving Motivation to Read and/or Write through Goal Setting - Rosentrater, Ashley (My University, 2015)
One essential component of reading and writing instruction is motivation. This study explored the impact of goal setting on motivation in reading and writing class in a fifth grade classroom in a rural community. Participants wrote goals weekly in their goal journal that was provided for them and reflected each day on if they were able to meet their goal for the day or what they could do to help attain their goal if they had not done it that day. Findings indicated that participants? motivation was impacted in their desire to want to read and/or write, participate in class discussions, and read a variety of materials during independent reading time.